(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background Optimization of stent deployment during percutaneous coronary intervention (PCI) is a key element for improving clinical outcomes but even in the DES era, optimal deployment of stents remains a challenging issue Objective to investigate whether the high inflation pressure stent deployment is enough for optimal deployment or routine post stenting noncompliant balloon dilation will be required Methods We included 60 patients with coronary artery disease who were subjected to elective stenting. Patients were divided into two groups: group A, high inflation pressure stent deployment (at 16-20 atm) followed by stent boost subtract imaging (SBS) assessment and if showing stent under-deployment, we added non-compliant balloon (NC) inflation at high pressure and group B, stent deployment was done at high pressure followed by routine NC balloon postdilatation at 18–20 atm. All stents were 2nd generation DES. Then both groups were assessed by IVUS MUSIC criteria & SBS optimal deployment criteria to determine the optimal deployment. Results The mean stent deployment pressure in group A (16.33±1.29) and mean duration of stent deployment in group A (29.07±4.25). There was no statistically significant difference between groups A and B regarding optimal stent deployment (P=1.000) and the occurrence of complications as spasm, dissection, acute stent thrombosis and no flow (P-value >0.05). The presence of heavy calcification was significantly associated with higher inflation pressure, longer inflation duration and significantly lower MSA/ARLA % (stent expansion) by IVUS in group A (P-value<0.05) and significantly associated with lower symmetry index in group B (P-value<0.05) and in group B the heavy calcification was associated significantly with dissection. Conclusion High-pressure stent deployment was associated with optimal stent deployment but heavy coronary calcification in lesion lead to less expansion and less symmetry of stent even after NC balloon dilatation and also heavy coronary calcification was associated with increased risk of complication as dissection, etc.